The PopN Gate-keeper Complex Acts on the ATPase PscN to Regulate the T3SS Secretion Switch from Early to Middle Substrates in Pseudomonas aeruginosa. Issue 24 (4th December 2020) - Ngo, Tuan-Dung; Perdu, Caroline; Jneid, Bakhos; Ragno, Michel; Novion Ducassou, Julia; Kraut, Alexandra; Couté, Yohann; Stopford, Charles; Attrée, Ina; Rietsch, Arne; Faudry, Eric
Graphical abstract: Highlights: T3SS substrates are secreted sequentially but information on the switches are missing. Interaction of the T3SS ATPase with secreted proteins were investigated by different approaches. Microscale Thermophoresis revealed a lower affinity for chaperones alone compared to complexes. The Gate-keeper complex binds to the ATPase and increases its affinity for the needle complex. A new role of the Gate-keeper complex is proposed, directly acting on the T3SS ATPase. Abstract: Pseudomonas aeruginosa is an opportunistic bacterium of which the main virulence factor is the Type III Secretion System. The ATPase of this machinery, PscN (SctN), is thought to be localized at the base of the secretion apparatus and to participate in the recognition, chaperone dissociation and unfolding of exported T3SS proteins. In this work, a protein–protein interaction ELISA revealed the interaction of PscN with a wide range of exported T3SS proteins including the needle, translocator, gate-keeper and effector. These interactions were further confirmed by Microscale Thermophoresis that also indicated a preferential interaction of PscN with secreted proteins or protein-chaperone complex rather than with chaperones alone, in line with the release of the chaperones in the bacterial cytoplasm after the dissociation from their exported proteins. Moreover, we suggest a new role of the gate-keeper complex and the ATPase in the regulation of early substrates recognition by the T3SS. This finding sheds a new light on the mechanism of secretion switching from early to middle substrates in P. aeruginosa .